LIGHTING STUDY IN CLASSROOM AT MTS AL MUTTAQIN PLEMAHAN KEDIRI - Pratama, M Risa Diki; Purnama, Muhammad Sega Sufia; Nugraha, Dian (Border: Jurnal Arsitektur, 2023)
Lighting is very important in the classroom. The layout or orientation, window openings and area of the building must be considered so that sunlight entering the classroom can meet the standart. The purpose of this study was to find out how much light intensity is in the classroom and whether it is in accordance with SNI standards, so that it is comfortable for learning. This research method uses qualitative methods by observing interviews and quantitative methods by using simulations. The results showed that first grade class has an average of 1000 lux for 08.00 AM however, towards 12.00 PM the intensity of incoming light decreases to an average of 100 lux. Second grade has an average of 500 lux for 08.00 AM but towards 12.00 PM the intensity of incoming light decreases until it has an average of 100 lux. Grade three has an average of 300 lux at 14.00 PM and towards 16.00 PM the light intensity only decreases slightly so that it has the same average. The results of the interviews showed a lack of lighting during learning activities. The conclusion is that the average intensity value in the class measured is sufficient, but the distribution is uneven, so artificial lighting is needed.